Bacterial biofilm: A novel antigen for oral vaccination of fish - Mamun, Md Abdullah Al; Nasren, Shamima; Rathore, Sanjay Singh; Rakesh, K; Pai, Manjulesh; Poojary, Sathish Rama (Bangladesh Journal of Zoology, 2018)
Abstract not available Bangladesh J. Zool. 45(2): 189-192, 2017